Ultrafast modulation of femtosecond laser pulses in direct-gap semiconductor metasurfaces with magnetic resonances - Zubyuk, Varvara V.; Shcherbakov, Maxim R.; Vabishchevich, Polina P.; Liu, Sheng; Vaskin, Aleksandr; Keeler, Gordon A.; Pertsch, Thomas; Dolgova, Tatyana V.; Staude, Isabelle; Brener, Igal; Fedyanin, Andrey A. (AIP Conference Proceedings, 2017)
We experimentally demonstrate ultrafast all-optical modulation in periodic arrays of subwavelength gallium arsenide nanodisks with localized Mie-type resonances. The efficient laser pulse modulation of up to 90% on the picosecond scale in the vicinity of the magnetic dipole resonance at a low pump fluence below 400 μJ/cm2 is shown by transient reflectance spectroscopy.
CRIS-Team Scopus Importer:2023-04-20